Analisis Disiplin Kerja dalam Upaya Meningkatkan Kinerja Karyawan Rezky Laundry - Almadi Destian; Robbi Zidni Ilma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study is to analyze how work discipline and efforts to improve employee performance at Rezky Laundry. This research uses a descriptive qualitative methodology, collecting data through documentation, interviews, and observations. Four employees and business owners were deliberately selected as research informants. Rezky Laundry, located in West Bandung Regency, was used as a research location, and Miles, Huberman, and Saldana triangulation analysis approaches were used to systematically process the data. The findings of the study show that Rezky Laundry employees continue to show poor work discipline, as seen from delays, non-compliance with SOPs, and lack of sense of responsibility. This has an impact on employee performance both in terms of productivity, punctuality, service quality, and customer satisfaction. In conclusion, poor work discipline has a direct negative impact on the quality of employee performance. Improvements in management systems, such as the development of written SOPs, the application of rewards and punishments, and repetitive discipline training, are recommended by researchers to improve operational effectiveness and employee professionalism.